Promising Techniques for Wastewater Treatment and Water Quality Assessment (IntechOpen, 2023)
This book reviews the primary aspects of wastewater treatment processing techniques and designs, as well as water quality assessment. Chapters address microwave digestive techniques of wastewater treatment, advanced ozone oxidative and photo processes, and reactive distillation for various applications. The book is a useful resource for choosing applicable processing techniques and design parameters.